Answer:
(3x + 1)^2
Explanation:
The first and last terms are perfect squares. From its structure, this is a perfect square trinomial.
All of the symbols in the expression 9x2 + 6x + 1 are positive, so use the rule for the square of the sum of two terms.
In the given expression, a2 = 9x2 and b2 = 1, so a = 3x and b = 1.
2ab = 2(3x)
= 6x
This result matches the middle term in the polynomial expression, 6x, so apply the rule for the square of the sum of two terms.
The expression 9x2 + 6x + 1 is equal to (3x + 1)2.